Antenatal Ovarian Torsion Presenting With Features of Intestinal Obstruction in a Neonate - Joshi, Jayateertha; Kamath, Nutan; Kini, Jyoti Ramnath; K, Jayashree; Rao, Suchetha; Kamath, Sowmini P (Journal of Nepal Paediatric Society, 2020)
With the advent of antenatal ultrasonography (USG), detection of neonatal intra-abdominal cystic lesions is on the rise. We present a neonate who was detected antenatally to have a cystic lesion per abdomen and presented with features of intestinal obstruction on first postnatal day. Emergency exploratory laparotomy revealed a left torsed ovarian cyst compressing the ileoceacal junction. Left oophorectomy was done and ovarian torsion was confirmed by histopathology examination. The USG abdomen at six months follow up showed a well visualised right ovary.